19 Years of Mortar Dating: Learning from Experience. Issue 2 (2014) - Ringbom, Åsa; Lindroos, Alf; Heinemeier, Jan; Sonck-Koota, Pia
Abstract : Since 1994, our team has gained extensive experience applying accelerator mass spectrometry (AMS) radiocarbon analysis for mortar dating, totaling over 465 samples and 1800+ measured CO2 fractions. Several samples have been analyzed repeatedly. The research covers both Medieval and Classical archaeology. We therefore believe our experience can be helpful when developing preparation procedures for different kinds of mortars in different areas and in varying chronologies. So far, the main areas of interest have been (a) the churches of the Åland Islands (in the archipelago between Finland and Sweden); (b) the churches in the Åboland Archipelago (SW Finland); (c) sites in the Iberian Peninsula including Torre de Palma (a Roman village in Portugal); and (d) Rome, Pompeii, and Herculaneum (Italy). Most of the analyses before 2000 were hydrolized in only two CO2 fractions per sample, and reliability criteria were defined on the basis of how well the ages of the two fractions agree with each other. These criteria have proved most helpful in determining the reliability of 14 C mortar analyses. Different types of mortar have been investigated, including lime mortars made both from limestone and marble, pozzolana mortars, fire-damaged mortars, and mortars based on burnt shells. Most importantly, separate lime lumps sampled from these mortars have been analyzed sporadically and recently more systematically. The research also includes different types of hydrolysis applied in the pretreatment. In addition to using 85% phosphoric acid (H3 PO4 ), the experimental research includes tests with smaller concentrations of phosphoric acid, and tests based on 2–3% hydrochloric acid (HCl) dissolutions. To characterize the dissolution process, results are presented as age profiles of 2–5 CO2 fractions. In our experience, pozzolana mortars have been difficult to date, and HCl dissolution should be used only in special cases and in complementary tests.